The immune synapse as a novel target for therapy - Graca, Luis, MD (PIR (Series), 2008)
The immune synapse can be compared to a molecular machine that controls T cell activation when getting in contact with an antigen-presenting cell (APC). The immune synapse is involved in the transfer of information across the T cell-APC junction. It plays an essential role in the control and nature of the immune response. In recent years several approaches have been developed to reprogramming the immune response by targeting molecules involved in the immune synapse. Monoclonal antibodies, such as the ones targeting the lymphocyte co-receptor, co-stimulatory and adhesion molecules (CD3, CD4, CD.